Inter-islands Dynamic Economy: Colonial Policy on the Indonesian Ports Development for International and Domestic Shipping During Colonial Times - Haryono Rinardi; Yety Rochwulaningsih (Diponegoro University, 2020)
As a capital-intensive transport technology linked to industrialized economies, ports become more essential economic infrastructure for developing periphery. Using the historical method, this article examines the relations between ports construction and the development of the voyages of the Indonesian archipelago, which was before called the Dutch East Indies. Based on the results, the port's construction caused by several factors. First, the colonial government wanted to reduce Singapore's role as an entre-port for the Dutch East Indies shipping activities, so that several ports been developed in the outer islands of Java. Second, ports development in outer islands became one of the Dutch economic expansions. Third, to relinquish reliance on foreign shipping companies, the colonial government then developed KPM and gave a monopoly right of shipping across the islands. Fourth, the utilization of modern ship engines in shipping led the growing up international voyages and had prompted the government to develop ports. Another interesting finding from this article is the relation between shipping and trade, the port constructions in various parts of the Dutch East Indies has encouraged trading networks developed in the area.